2022
DOI: 10.5089/9798400215698.001
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Multipliers During Pandemics

Abstract: Many countries have deployed substantial fiscal packages to cushion the economic fallout from the COVID-19 pandemic. A historical look at past pandemics and epidemics highlights concomitant public sector support in response to health crises. This paper assesses how fiscal multipliers could vary during health crises, particularly how factors such as social distancing and uncertainty could lower contemporaneous (T) multipliers and increase near-term (T+1 and T+2) multipliers as economies re-open, including due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…Empirical studies, such as those by Kinda et al (2022) and Diallo and Mendy (2018), provide tangible evidence supporting the theoretical constructs. Kinda et al (2022) empirically demonstrate the challenges posed by fiscal dominance in influencing economic outcomes, offering a bridge between theory and real-world implications.…”
Section: Theoretical Foundation and Reviewmentioning
confidence: 80%
See 1 more Smart Citation
“…Empirical studies, such as those by Kinda et al (2022) and Diallo and Mendy (2018), provide tangible evidence supporting the theoretical constructs. Kinda et al (2022) empirically demonstrate the challenges posed by fiscal dominance in influencing economic outcomes, offering a bridge between theory and real-world implications.…”
Section: Theoretical Foundation and Reviewmentioning
confidence: 80%
“…Empirical studies, such as those by Kinda et al (2022) and Diallo and Mendy (2018), provide tangible evidence supporting the theoretical constructs. Kinda et al (2022) empirically demonstrate the challenges posed by fiscal dominance in influencing economic outcomes, offering a bridge between theory and real-world implications. Diallo and Mendy (2018) and Jazbec and Banerjee (2017) contribute by empirically examining the impact of fiscal dominance on inflation expectations, emphasising the need for the theoretical frameworks to guide policy coordination.…”
Section: Theoretical Foundation and Reviewmentioning
confidence: 80%
“…They steadily increase if the initial spending shock occurs in a recession while they steadily decline if the shock happens in an expansion (Auerbach and Gorodnichenko, 2012). A more recent study (Kinda, Lengyel, and Chahande, 2022) has found that during health crises, social distancing and uncertainty may lower multipliers which then increase in magnitude as economies re-open and pent-up demand is unleashed.…”
Section: International Monetary Fund 14mentioning
confidence: 99%
“…It was found that expenditures related to healthcare rose by 9.7% in 2020, a far faster rate as compared to a 4.3% rise in 2019, primarily due to a 36% rise in federal outlays allocated to healthcare to cope with the COVID-19 pandemic. Kinda et al (2022) evaluated the influence of fiscal multipliers in the phase of health crises like the COVID-19 pandemic, compared to normal times. It was observed that fiscal multipliers were significantly larger in the year following a health crisis, especially in advanced economies.…”
Section: Literature Reviewmentioning
confidence: 99%